Temporal evolution of the ozone concentration in the troposphere - Concepción, Lía (2016)
This research allows studying the evolution of the ozone concentration in the troposphere using the Polymath simulation software, considering the reaction mechanisms that involve the generation of ozone from the knowledge of the values ​​of the kinetic constants. This software simply encodes the differential equations from the matter balances involved with ozone formation. From the proposed dispersion models, the Batch reactor and the semi-continuous reactor in the predominant direction of the wind have been considered to obtain the chemical equations in each case under the conditions of thermal inversion and in a second case without these conditions. . The forecast allows to know in advance the ozone concentrations at different times of the day, to obtain an early warning of the concentration levels and take the necessary personal precautions; It will also save resources compared to experimental measurements. Finally, the evolution of the ozone concentration can be obtained at any time of the day, which will serve to know if it is within the permissible values ​​as a secondary pollutant in the atmosphere and thus carry out the corresponding actions to control pollution atmospheric and the impact on environmental quality.